Participation and the politics of mediation: The case of the Thembelihle Crisis Committee - Lourenco, Marisa (My University, 2018)
The government’s distaste for informality in the new South Africa despite the rights of public participation and the possibility of in situ upgrading enshrined in policy and legislated, has seen a severe disconnect emerge between the state and informal settlements. This can be observed in the Thembelihle informal settlement in Gauteng, which has seen residents mobilise to form the Thembelihle Crisis Committee to articulate their struggle and make their demands heard through numerous channels. Given the market principles guiding the public service sector through the adoption of New Public Management, it is worth a closer interrogation on how these misguide participatory processes in the South Africa, and how they can be understood and interrogated in the context of this grassroots organisation.
A research report submitted to the Faculty of Engineering and the Built Environment at the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Urban Studies, 2018